2019
DOI: 10.1101/521070
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multiple phase-variable mechanisms, including capsular polysaccharides, modify bacteriophage susceptibility in Bacteroides thetaiotaomicron

Abstract: 21A variety of cell surface structures, including capsular polysaccharides (CPS), dictate 22interactions between bacteria and their environment including their viruses (bacteriophages). 23Members of the prominent human gut Bacteroidetes characteristically produce several phase-24 variable CPS, but their contributions to bacteriophage interactions are unknown. We used 25 engineered strains of the human symbiont Bacteroides thetaiotaomicron, which differ only in the 26 CPS they express, to isolate bacteriophages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 61 publications
0
19
0
Order By: Relevance
“…Despite nearly a century of pioneering molecular work, the mechanistic insights into phage specificity for a given host, infection pathways, and the breadth of bacterial responses to different phages have largely focused on a handful of individual bacterium-phage systems [9][10][11][12][13]. Bacterial sensitivity/resistance to phages is typically characterized using phenotypic methods such as cross-infection patterns against a panel of phages [14][15][16][17][18][19][20][21][22][23][24][25][26][27] or by whole-genome sequencing of phage-resistant mutants [28][29][30][31][32]. As such, our understanding of bacterial resistance mechanisms against phages remains limited, and the field is therefore in need of improved methods to characterize phage-host interactions, determine the generality and diversity of phage resistance mechanisms in nature, and identify the degree of specificity for each bacterial resistance mechanism across diverse phage types [13,25,26,[33][34][35][36][37][38][39][40][41][42][43][44][45][46][47].…”
Section: Introductionmentioning
confidence: 99%
“…Despite nearly a century of pioneering molecular work, the mechanistic insights into phage specificity for a given host, infection pathways, and the breadth of bacterial responses to different phages have largely focused on a handful of individual bacterium-phage systems [9][10][11][12][13]. Bacterial sensitivity/resistance to phages is typically characterized using phenotypic methods such as cross-infection patterns against a panel of phages [14][15][16][17][18][19][20][21][22][23][24][25][26][27] or by whole-genome sequencing of phage-resistant mutants [28][29][30][31][32]. As such, our understanding of bacterial resistance mechanisms against phages remains limited, and the field is therefore in need of improved methods to characterize phage-host interactions, determine the generality and diversity of phage resistance mechanisms in nature, and identify the degree of specificity for each bacterial resistance mechanism across diverse phage types [13,25,26,[33][34][35][36][37][38][39][40][41][42][43][44][45][46][47].…”
Section: Introductionmentioning
confidence: 99%
“…We demonstrate that BV01 is transducible in a gnotobiotic mouse model, suggesting that an unknown mammalian host factor is required for novel BV01 infection. Enigmatic infection dynamics may be the result of the phase variable polysaccharide capsule, as recent work suggests heterogeneity in capsular composition hinders phage infection on population-scales (17). Indeed, it has long been observed that finding phages in the Bacteroides using traditional techniques is difficult or impossible for most host strains (65, 66), making the host-first approach to phage discovery used here especially appealing.…”
Section: Discussionmentioning
confidence: 99%
“…The genus is known to degrade a diversity of complex carbohydrates (9, 10), and interact with host immune cells (11, 12). Within a single human host, many Bacteroides species and strains coexist, competing for nutrients under changing environmental conditions caused by host diet (13), host metabolites (14), host immune system activities (15, 16), and phage predation (17). Moreover, horizontal gene transfer plays an important role in shaping the evolution and function of Bacteroides genomes (18, 19).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations